Susceptibility to Amoxicillin-Clavulanate-Induced Liver Injury is Influenced by Multiple HLA Class I and II Alleles - Lucena-González, María Isabel; Molokhia, Mariam; Shen, Y; Urban, TJ; Aithal, Guruprasad P.; Andrade-Bellido, Raúl Jesús; Day, CP; Ruiz-Cabello, Francisco; Donaldson, PT; Stephens, Camilla; Munir, Pirmohamed; Romero-Gomez, Manuel; et al. (Elsevier, 2011)
Background & Aims: Drug-induced liver injury (DILI), especially from antimicrobial agents, is an important cause of serious liver disease. Amoxicillin-clavulanate (AC) is a leading cause of idiosyncratic DILI, but little is understood about genetic susceptibility to this adverse reaction. Methods: We performed a genome-wide association study using 822,927 singlenucleotide polymorphism (SNP) markers from 201 White European and US cases of ACDILI and 532 population controls, matched for genetic background.

Results: AC-DILI was associated with many loci in the major histocompatibility complex. The strongest effect was with a human leukocyte antigen (HLA) class II SNP (rs9274407, P=4.8×10−14), which correlated with rs3135388, a tag SNP of HLADRB1*1501-DQB1*0602 that was previously associated with AC-DILI. Conditioned on rs3135388, rs9274407 is still significant (P=1.1×10−4). An independent association was observed in the class I region (rs2523822, P=1.8×10−10), related to HLA-A*0201. The most significant class I and II SNPs showed statistical interaction (P=0.0015). Highresolution HLA genotyping (177 cases and 219 controls) confirmed associations of HLAA*0201 (P=2×10−6) and HLA-DQB1*0602 (P=5×10−10), and their interaction (P=0.005). Additional, population-dependent effects were observed in HLA alleles with nominal significance. In an analysis of auto-immunerelated genes, rs2476601 in the gene PTPN22 was associated (P=1.3×10−4).

Conclusions: Class I and II HLA genotypes affect susceptibility to AC-DILI, indicating the importance of the adaptive immune response in pathogenesis. The HLA genotypes identified will be useful in studies of the pathogenesis of AC-DILI, but have limited utility as predictive or diagnostic biomarkers because of the low positive-predictive values
https://openpolicyfinder.jisc.ac.uk/id/publication/4770
Keywords: Hepatotoxicidad; Medicamentos - Efectos secundarios; Farmacogenética; Hepatotoxicity; GWAS; MHC; Pharmacogenomics; Side effect